2022
DOI: 10.1002/app.52314
|View full text |Cite
|
Sign up to set email alerts
|

Voltage stabilizer and nanofiller in enhancement of insulation properties of cross‐linked polyethylene

Abstract: This paper investigates the influence of voltage stabilizer and nanofiller addition on the insulation performance of the cross-linked polyethylene (XLPE). The test samples of XLPE/stabilizer blends consisting of 1 wt% maminobenzoic acid, XLPE nanocomposites consisting of 0.5 wt% nano MgO and XLPE hybrid composite consisting of both voltage stabilizer and nanofillers were prepared. Various physicochemical and electrical properties were measured to analyze the performance of prepared samples. The obtained result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One approach to the development of new high breakdown strength material is compounding voltage stabilizer molecules into polyethylene, which can then be further crosslinked. [2][3][4][5][6][7][8][9] Chen and co-workers 7 have also tried to use nanofillers in cross-linked polyethylene and found that the addition of nanofillers typically will decrease the electrical insulation performance. The study of voltage stabilizers has a history of more than half a century.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to the development of new high breakdown strength material is compounding voltage stabilizer molecules into polyethylene, which can then be further crosslinked. [2][3][4][5][6][7][8][9] Chen and co-workers 7 have also tried to use nanofillers in cross-linked polyethylene and found that the addition of nanofillers typically will decrease the electrical insulation performance. The study of voltage stabilizers has a history of more than half a century.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐linked polyethylene is an important and widely utilized material for power transmission cables. One approach to the development of new high breakdown strength material is compounding voltage stabilizer molecules into polyethylene, which can then be further cross‐linked 2–9 . Chen and co‐workers 7 have also tried to use nanofillers in cross‐linked polyethylene and found that the addition of nanofillers typically will decrease the electrical insulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…LDPE and XLPE feature values of σ DC ≥ 10 −14 S m −1 at 30 kV mm −1 and 70 °C, 10 which are common design parameters for the highest electric field stress and operating temperature that the insulation layer of an HVDC cable may experience. 8 Conductivity-reducing additives such as metal oxide nanoparticles, 11 organic semiconductors including fullerenes 12 and conjugated polymers, 13 aromatic voltage stabilizers, [14][15][16] as well as high-density polyethylene (HDPE) 10 can be added to the polyethylene-based insulation material to achieve a further reduction in σ DC . Moreover, the combination of different additives such as Al 2 O 3 nanoparticles and HDPE can give rise to a synergistic conductivity-reducing effect.…”
Section: Introductionmentioning
confidence: 99%